A photocatalyst and its production method and application
By precipitating and recycling ThO2 and rare earth oxides in monazite tailings, and reacting with tetrabutyl titanate and other substances to form a doped titanium dioxide photocatalyst, the problems of element waste and environmental pollution in monazite tailings are solved and achieved. Efficient element recovery and photocatalytic degradation effect.
Patent Information
- Application Number
- CN202410791134.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-06-19
AI Technical Summary
The tailings of the monazite contain a large amount of ThO2 and rare earth oxides, resulting in waste of rare earth elements and thorium elements and adversely affecting the environment.
By grinding the monazite tailings into powder, dissolving it in nitric acid, filtering and adding oxalic acid solution for precipitation and recovery, and then reacting with tetrabutyl titanate and other substances to form a doped titanium dioxide photocatalyst.
It achieves the recovery of more than 98% of thorium and rare earth elements, and forms a photocatalyst with efficient photocatalytic degradation effect, reducing environmental pollution.
Smart Images

Figure CN118831603B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for producing a photocatalyst by utilizing monazite tailings. Background Art
[0002] Monazite is a major rare earth mineral, and its crystal form belongs to the monoclinic system and monoclinic columnar crystal type. A large number of enterprises in my country use monazite as raw material for rare earth smelting. When smelting rare earths, the monazite concentrate is generally decomposed by alkali to extract useful rare earths and phosphorus from the liquid feed. The remaining monazite tailings contain a large amount of ThO2 and a certain proportion of rare earth oxides (REO), which not only wastes rare earth elements, but also wastes a large amount of thorium. Thorium can not only be used to prepare high-strength metal materials and raw materials for advanced lenses, but also can be used as a raw material for nuclear fuel U-233. Therefore, if these monazite tailings are not effectively recycled and reused, it will not only cause a waste of monazite resources, but also cause great adverse effects on the environment. Summary of the invention
[0003] In order to make full use of monazite, reduce waste and reduce adverse impacts on the environment, the present application first proposes a method for producing a photocatalyst, which comprises the following steps:
[0004] (1) grinding the monazite tailings into monazite powder, then adding the monazite powder into nitric acid to completely dissolve the monazite powder, and filtering to obtain a first filtrate and a first filter residue;
[0005] Adding oxalic acid solution to the first filtrate to generate oxalate precipitation, filtering the solution after the precipitation is completed to obtain a secondary filtrate and a secondary filter residue, and evaporating and drying the secondary filtrate to obtain a dopant;
[0006] (2) adding tetrabutyl titanate to anhydrous ethanol, then adding glacial acetic acid, and dropwise adding hydrochloric acid to make the pH of the solution ≤ 3, and then mixing well to prepare solution A;
[0007] Add the dopant into solution A and stir evenly to obtain solution B;
[0008] Add the ethanol aqueous solution dropwise to solution B, keep stirring, and obtain a sol;
[0009] (3) aging the sol at room temperature to obtain a gel, and then washing, drying, calcining and grinding the gel to obtain a photocatalyst. In step (2), the hydrochloric acid is added dropwise mainly to make the pH of the solution ≤ 3. There is no special requirement for the concentration of the hydrochloric acid used. This application specifically uses 1-6 mol / L hydrochloric acid.
[0010] In this application, two filtrations were performed, of which the first filtration was mainly to remove the insoluble matter contained in the monazite tailings to prevent these insoluble matter from entering the photocatalyst. Oxalic acid was used to precipitate and recover thorium and rare earth elements. The secondary filtrate produced after the recovery of thorium and rare earth elements evaporated to form dopants, which still contained trace amounts of thorium and rare earth elements, as well as other symbiotic elements, such as oxides of silicon, titanium, lead, zirconium, calcium, iron, magnesium, sodium, aluminum and other elements. Among these elements, except for titanium, other elements also participate in the doping of titanium dioxide, and the titanium element therein will also become titanium dioxide and become a doped body. In the reaction process with titanium dioxide, a complex doping structure is formed, which has a good photocatalytic degradation effect on methylene blue.
[0011] Since the above-mentioned elements accumulate in the same mineral, they can replace each other between similar particles in the mineral lattice without changing the mineral structure. These elements are usually not the main and stable components in the mineral lattice, but because their crystal chemical properties are similar to the crystal chemical properties of a main element in the mineral, under certain conditions, they enter the mineral lattice in the form of minor elements or trace elements. After entering the mineral lattice, these elements do not change the crystal structure of the mineral. Therefore, the trace elements in the same mineral can dope the same crystal to different degrees to form a co-doped structure.
[0012] However, some of the above-mentioned metal elements may not be combined with titanium dioxide in the form of doping. For example, SiO2 and ZrO2, these two oxides are insulators, and they may mainly play the role of carriers to increase the pore size and specific surface area of the photocatalyst. TiO2 particles will be adsorbed inside SiO2 and ZrO2 to increase the contact area with methylene blue, thereby improving the degradation effect of methylene blue.
[0013] Other elements, as symbiotic elements, have similar properties in some aspects and can be doped with titanium dioxide. For example, calcium, iron, magnesium, aluminum, lanthanum, cerium and other elements can be doped with titanium dioxide, thereby introducing defects in the TiO2 semiconductor or changing the crystallinity, thereby changing the structure and surface properties of the particles. This can not only affect the recombination rate of electrons and holes, but also expand the absorption wavelength range of TiO2 to the visible light region, promote the separation of photogenerated electrons and holes, and improve the efficiency of light energy conversion and utilization, thereby ultimately enhancing the activity of the photocatalyst.
[0014] By using the present application, not only can more than 98% of thorium and rare earth elements be recovered, but also the remaining substances that are difficult to recover can be doped with titanium dioxide to form a photocatalyst for the degradation of methylene blue. The degradation efficiency can reach more than 98%, which not only reduces the pollution to the environment, but also provides a new structure of doped titanium dioxide photocatalyst, broadening the types of titanium dioxide photocatalysts.
[0015] Specifically, to ensure the full dissolution of monazite powder and the recovery of thorium and other rare earth elements, in step (1), the mass ratio of monazite powder to nitric acid is 1:(25-30), and the concentration of nitric acid is 60-68wt%; the mass ratio of monazite powder to oxalic acid is 1:(1.7-2.0), and the concentration of oxalic acid is 9-12wt%.
[0016] Specifically, in order to properly use the production method in the present application, the monazite tailings contain 20-32wt% ThO2, 2.2-3wt% CeO2, 1.5-2.2wt% TiO2, 1.6-2.3wt% P2O5, 0.6-0.9wt% La2O3, 0.4-0.6wt% PbO, and 0.2-0.3wt% ZrO2 in terms of oxides. The monazite tailings with the above composition can well recycle thorium and rare earth elements, and can form a photocatalyst with a photocatalytic effect.
[0017] Specifically, in order to fully dissolve tetrabutyl titanate and avoid wasting anhydrous ethanol, in step (2), the mass ratio of tetrabutyl titanate, anhydrous ethanol and glacial acetic acid is 1:(3-5):(0.15-0.2).
[0018] Specifically, in step (2), the mass ratio of the dopant to tetrabutyl titanate is 1:(0.9-1.2) based on the monazite tailings. When the proportion of the dopant is low, the effect of the photocatalyst will be reduced. When the proportion of the dopant is too high, the photocatalytic efficiency of the photocatalyst will no longer increase, but will slowly decrease. When the proportion of monazite is too low, the doping ratio of the photocatalyst will be too low, and the catalytic effect of the photocatalyst cannot be effectively improved. However, when the proportion of monazite is too high, the doping ratio of the photocatalyst will be too large. The excessive doping ratio may cause the deformation of the titanium dioxide lattice, and may also cause the titanium dioxide to transform from anatase to rutile. The photocatalytic performance of the rutile crystal is weaker than that of the anatase, thereby reducing the degradation efficiency of the photocatalyst.
[0019] Specifically, in order to facilitate the control of the reaction, in step (2), the ethanol aqueous solution is prepared by anhydrous ethanol and distilled water in a volume ratio of (3-5):1; the volume ratio of water to tetrabutyl titanate in the ethanol aqueous solution is (1-1.5):1
[0020] Specifically, in step (3), the aging time of the gel is 20-30 hours, the drying temperature is 80-100° C., the drying time is 4-6 hours, the calcination temperature is 350-450° C., and the calcination time is 3-4 hours.
[0021] Secondly, the application also discloses a photocatalyst prepared by any of the above production methods.
[0022] Again, the present application also discloses the application of the above-mentioned photocatalyst in wastewater treatment. Specifically, the wastewater is wastewater containing methylene blue, the concentration of methylene blue in the wastewater is 1-27.5 mg / L, and the concentration of the photocatalyst in the wastewater is 0.20-0.55 g / L.
[0023] When the photocatalyst provided in the present application is used to degrade methylene blue in wastewater, when the concentration of methylene blue is lower than 25 mg / L and the amount of photocatalyst used is 20 times the total amount of methylene blue, the degradation rate of methylene blue can reach more than 98% within 120 minutes, with high degradation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the SEM microscopic morphology of the 1# photocatalyst prepared in Example 1.
[0025] Figure 2 It is the X-ray diffraction (XRD) pattern of monazite tailings.
[0026] Figure 3 This is the X-ray diffraction (XRD) pattern of the 1# photocatalyst prepared in Example 1.
[0027] Figure 4 This is the EDS test diagram of monazite tailings.
[0028] Figure 5 This is the EDS test image of the 1# photocatalyst prepared in Example 1.
[0029] Figure 6 This is the catalytic efficiency curve of 1-7# photocatalyst. DETAILED DESCRIPTION
[0030] Example 1
[0031] Preparation of 1# photocatalyst:
[0032] (1) Grinding 2 g of monazite tailings into monazite powder, then adding the monazite powder into 50 g of 68 wt% nitric acid to completely dissolve the monazite powder, filtering, and obtaining a first filtrate and a first filter residue; in terms of oxides, the monazite tailings contain 21.5 wt% ThO2, 2.43 wt% CeO2, 1.68 wt% TiO2, 1.69 wt% P2O5, 0.78 wt% La2O3, 0.55 wt% PbO, and 0.21 wt% ZrO2.
[0033] 3.4 g of 10 wt% oxalic acid solution is added to the first filtrate to produce oxalate precipitation. When the precipitation is completed, the solution is filtered to obtain a secondary filtrate and a secondary filter residue. The secondary filtrate is evaporated and dried to obtain a dopant. The main component of the oxalate precipitation is thorium oxalate, and contains a small amount of cerium oxalate, lanthanum oxalate and other oxalates.
[0034] The dopant contains 2 mg Th, 0.81 mg Ce and 0.62 mg La. The recovery rates of Th, La and Ce are over 99%, 97% and 95% respectively.
[0035] (2) adding 2 g of tetrabutyl titanate to 7 g of anhydrous ethanol, and then adding 0.3 g of glacial acetic acid, and dropping 3 mol / L of hydrochloric acid to adjust the pH of the solution to 2.5-3, and mixing well to prepare solution A;
[0036] Add the dopant into solution A and stir evenly to obtain solution B;
[0037] 9 mL of ethanol aqueous solution was added dropwise to solution B, and stirring was continued to obtain a sol; the volume ratio of anhydrous ethanol to distilled water in the ethanol aqueous solution was 3:1.
[0038] (3) The sol was aged at room temperature for 24 hours to obtain a gel, and then the gel was washed with distilled water to remove the salt in the gel. After washing, the gel was dried at 80°C for 6 hours, and then calcined at 400°C for 4 hours to obtain 1# photocatalyst.
[0039] Example 2
[0040] Preparation of 2# photocatalyst:
[0041] (1) Grinding 2 g of monazite tailings into monazite powder, then adding the monazite powder into 60 g of 60 wt% nitric acid to completely dissolve the monazite powder, filtering to obtain a first filtrate and a first filter residue; in terms of oxides, the monazite tailings contain 30.1 wt% ThO2, 2.56 wt% CeO2, 1.99 wt% TiO2, 2.01 wt% P2O5, 0.88 wt% La2O3, 0.41 wt% PbO, and 0.28 wt% ZrO2.
[0042] 3.6 g of 12 wt% oxalic acid solution is added to the first filtrate to produce oxalate precipitation. When the precipitation is completed, the solution is filtered to obtain a secondary filtrate and a secondary filter residue. The secondary filtrate is evaporated and dried to obtain a dopant. The main component of the oxalate precipitation is thorium oxalate, and contains a small amount of cerium oxalate, lanthanum oxalate and other oxalates.
[0043] The dopant contains 2.2 mg Th, 0.77 mg Ce and 0.58 mg La. The recovery rates of Th, La and Ce are over 99%, 98% and 96% respectively.
[0044] (2) adding 2.4 g of tetrabutyl titanate to 10 g of anhydrous ethanol, and then adding 0.4 g of glacial acetic acid, and dropping 3 mol / L of hydrochloric acid to adjust the pH of the solution to 2-2.5, and mixing well to prepare solution A;
[0045] Add the dopant into solution A and stir evenly to obtain solution B;
[0046] 14 mL of ethanol aqueous solution was added dropwise to solution B, and stirring was continued to obtain a sol; the volume ratio of anhydrous ethanol to distilled water in the ethanol aqueous solution was 3:1.
[0047] (3) The sol was aged at room temperature for 30 hours to obtain a gel, and then the gel was washed with distilled water to remove the salt in the gel. After washing, the gel was dried at 100°C for 4 hours, and then the gel was calcined at 450°C for 3 hours to obtain a 2# photocatalyst.
[0048] Example 3
[0049] Preparation of 3# photocatalyst:
[0050] (1) Grinding 2 g of monazite tailings into monazite powder, then adding the monazite powder into 55 g of 65 wt% nitric acid to completely dissolve the monazite powder, filtering to obtain a first filtrate and a first filter residue; in terms of oxides, the monazite tailings contain 27.9 wt% ThO2, 2.81 wt% CeO2, 2.18 wt% TiO2, 2.27 wt% P2O5, 0.61 wt% La2O3, 0.58 wt% PbO, and 0.22 wt% ZrO2.
[0051] 4 g of 9 wt% oxalic acid solution is added to the first filtrate to produce oxalate precipitation. When the precipitation is completed, the solution is filtered to obtain a secondary filtrate and a secondary filter residue. The secondary filtrate is evaporated and dried to obtain a dopant. The main component of the oxalate precipitation is thorium oxalate, and contains a small amount of cerium oxalate, lanthanum oxalate and other oxalates.
[0052] The dopant contains 1.8 mg Th, 0.83 mg Ce and 0.65 mg La. The recovery rates of Th, La and Ce are over 99%, 98% and 94% respectively.
[0053] (2) adding 1.9 g of tetrabutyl titanate to 9 g of anhydrous ethanol, and then adding 0.3 g of glacial acetic acid, and dropping 3 mol / L of hydrochloric acid to adjust the pH of the solution to 2-2.2, and mixing well to prepare solution A;
[0054] Add the dopant into solution A and stir evenly to obtain solution B;
[0055] 15 mL of ethanol aqueous solution was added dropwise to solution B, and stirring was continued to obtain a sol; the volume ratio of anhydrous ethanol to distilled water in the ethanol aqueous solution was 5:1.
[0056] (3) The sol was aged at room temperature for 20 h to obtain a gel, which was then washed with distilled water to remove the salt in the gel. After washing, the gel was dried at 90°C for 5 h, and then calcined at 350°C for 4 h to obtain a 3# photocatalyst.
[0057] Example 4
[0058] Preparation of 4# photocatalyst:
[0059] (1) Grinding 2 g of monazite tailings into monazite powder, then adding the monazite powder into 60 g of 68 wt% nitric acid to completely dissolve the monazite powder, filtering to obtain a first filtrate and a first filter residue; in terms of oxides, the monazite tailings contain 26.6 wt% ThO2, 2.75 wt% CeO2, 1.57 wt% TiO2, 1.80 wt% P2O5, 0.67 wt% La2O3, 0.51 wt% PbO, and 0.22 wt% ZrO2.
[0060] 3.8 g of 11 wt% oxalic acid solution is added to the first filtrate to produce oxalate precipitation. When the precipitation is completed, the solution is filtered to obtain a secondary filtrate and a secondary filter residue. The secondary filtrate is evaporated and dried to obtain a dopant. The main component of the oxalate precipitation is thorium oxalate, and contains a small amount of cerium oxalate, lanthanum oxalate and other oxalates.
[0061] The dopant contains 2.5 mg Th, 0.85 mg Ce and 0.63 mg La. The recovery rates of Th, La and Ce are over 99%, 98% and 94% respectively.
[0062] (2) Add 2.2 g of tetrabutyl titanate to 11 g of anhydrous ethanol, then add 0.4 g of glacial acetic acid, add 3 mol / L hydrochloric acid dropwise to adjust the pH of the solution to 2.5-2.8, and mix well to obtain solution A;
[0063] Add the dopant into solution A and stir evenly to obtain solution B;
[0064] 15 mL of ethanol aqueous solution was added dropwise to solution B, and stirring was continued to obtain a sol; the volume ratio of anhydrous ethanol to distilled water in the ethanol aqueous solution was 4.5:1.
[0065] (3) The sol was aged at room temperature for 30 hours to obtain a gel, and then the gel was washed with distilled water to remove the salt in the gel. After washing, the gel was dried at 95°C for 4 hours, and then calcined at 420°C for 3.5 hours to obtain a 4# photocatalyst.
[0066] Comparative Example 1
[0067] Preparation of 5# photocatalyst:
[0068] (1) 2 g of tetrabutyl titanate was added to 7 g of anhydrous ethanol, and then 0.3 g of glacial acetic acid was added, and 3 mol / L of hydrochloric acid was added dropwise to adjust the pH of the solution to 2.5-3, and the mixture was mixed uniformly to prepare solution A;
[0069] 9 mL of ethanol aqueous solution was added dropwise to solution B, and stirring was continued to obtain a sol; the volume ratio of anhydrous ethanol to distilled water in the ethanol aqueous solution was 3:1.
[0070] (2) The sol was aged at room temperature for 24 hours to obtain a gel, the gel was dried at 80°C for 6 hours, and then the gel was calcined at 400°C for 4 hours to obtain a 5# photocatalyst. This comparative example adopts the method of Example 1 to prepare a pure TiO2 photocatalyst without dopants.
[0071] Comparative Example 2
[0072] Preparation of 6# photocatalyst:
[0073] This comparative example is basically the same as Example 1, and the only difference is the amount of monazite tailings used. In this comparative example, the amount of monazite tailings used is 2.8 g.
[0074] Comparative Example 3
[0075] Preparation of 7# photocatalyst:
[0076] This comparative example is basically the same as the embodiment, and the only difference is the amount of monazite tailings used. In this comparative example, the amount of monazite tailings used is 1.4 g.
[0077] Figure 1 (a) and Figure 1 (b) are SEM microscopic morphology images of 1# photocatalyst. The shape of the catalyst particles is irregular, which may be caused by the breakage of the product particles during grinding.
[0078] See also Figure 2 and Figure 3 ,in Figure 2 is the XRD pattern of monazite tailings, Figure 3 This is the XRD pattern of 1# photocatalyst. Figure 3 The diffraction peaks observed at 25.3°, 37.9°, 48.0°, 54.2° and 62.6° match the anatase phase of TiO2 (JCPDS21-1272), corresponding to the (101), (004), (200), (105) and (204) crystal planes, respectively. Compared with the rutile phase, the anatase phase of TiO2 has superior photocatalytic activity. Figure 3 The diffraction peaks in the spectrum are not very sharp, indicating that the photocatalyst particles are very small. The additional peaks observed are attributed to the dopants produced by monazite tailings.
[0079] See also Figure 4 and Figure 5 ,in Figure 4 This is the EDS test diagram of monazite tailings. Figure 5 This is the EDS test image of the 1# photocatalyst prepared in Example 1. Figure 4 and Figure 5It can be seen that in addition to Th, Ti, La, and Ce elements, there are also trace amounts of Ca, Mg, Pb, Si, Zr, P, Cl and other elements in the photocatalyst, indicating that the doping of the photocatalyst prepared in the present application is multi-element co-doping.
[0080] Degradation effect detection:
[0081] In the present invention, the photocatalytic efficiency of the photocatalyst is evaluated by observing the degradation of the methylene blue solution. First, 100 mL of methylene blue solution (10 mg / L) was poured into a jacketed beaker, and 20 mg of the photocatalyst was added, and stirred in a dark room for 30 min to establish adsorption-desorption equilibrium through dark reaction.
[0082] Then, turn on the 300W xenon lamp located 25 cm above the jacketed beaker, and start the circulating water pump connected to the jacketed beaker at the same time, so that the solution in the jacketed beaker is at room temperature to avoid the influence of thermal effect on the photocatalytic performance of the sample.
[0083] 5 ml of sample was extracted from the suspension every 30 minutes, and then separated by a water filter membrane to obtain a clear solution. The clear solution was then analyzed using a spectrophotometer to test the absorbance of the liquid, thereby providing the photocatalytic efficiency of the photocatalyst.
[0084] The above method was used to measure the final catalytic efficiency of photocatalysts 1-7 ((C0-C) / C0×100%, where C: the concentration of methylene blue in the supernatant at a certain time point, C0: the concentration of methylene blue at the beginning of the reaction). The results are as follows: Figure 6 shown.
[0085] Photocatalysts #1-4 showed good catalytic degradation effects. When the illumination time was 120 minutes, the degradation efficiency of photocatalyst #1 was 99.1%, the degradation efficiency of photocatalyst #2 was 98.5%, the degradation efficiency of photocatalyst #3 was 98.7%, the degradation efficiency of photocatalyst #4 was 98.3%, the degradation efficiency of photocatalyst #5 was 58.6%, the degradation efficiency of photocatalyst #6 was 85.5%, and the degradation efficiency of photocatalyst #7 was 79.3%.
[0086] According to the above degradation efficiency, when the proportion of monazite is too low, the doping ratio of the photocatalyst will be too low, and the catalytic effect of the photocatalyst cannot be effectively improved. However, when the proportion of monazite is too high, the doping ratio will be too large. Excessive doping ratio may cause deformation of the titanium dioxide lattice and may also cause titanium dioxide to transform from anatase to rutile. The photocatalytic performance of rutile is weaker than that of anatase, which leads to a decrease in the degradation efficiency of the photocatalyst.
[0087] Using the above detection method, 100mL of methylene blue solution with concentration distribution of 5mg / L, 8mg / L, 10mg / L, 11mg / L, and 13mg / L was poured into 5 beakers respectively, and 20mg of the 1# photocatalyst prepared in Example 1 was added into 5 beakers respectively, and then the degradation rate of each methylene blue within 120 minutes was detected, and each degradation rate was 99.2%, 99.5%, 99.1%, 97.5%, and 86.1%, respectively, and each data is listed in Table 1. It was found that when the concentration of methylene blue reached 11mg / L, its degradation rate began to decrease, and after reaching 13mg / L, the rate of decrease of the degradation rate increased.
[0088] Table 1
[0089] Methylene blue concentration (mg / L) Degradation efficiency (%) 5 99.2 8 99.5 10 99.1 11 97.5 13 86.1
[0090] Using the above detection method, 100mL of methylene blue solution with a concentration distribution of 10mg / L was poured into 5 beakers respectively, and then 16mg, 18mg, 20mg, 22mg, 25mg and 30mg of 1# photocatalyst were added into 5 beakers respectively, and then the degradation rate of each methylene blue within 120 minutes was detected, and the degradation rates were 75.7%, 86.5%, 99.1%, 99.2%, 99.1% and 91.2% respectively. It was found that when the amount of photocatalyst reached 20mg, the degradation of 10mg / L methylene blue solution could reach the best effect in 120 minutes. With the increase of the amount of catalyst, the photocatalytic degradation effect remained unchanged at first, and then began to decrease. It should be that the photocatalyst with too high a concentration had an effect on the illumination. Excessive use of catalyst will also cause waste. Considering the comprehensive degradation ability and economic factors, the best time is when the amount of catalyst is 20mg. That is, when the catalyst concentration is 0.20 g / L and the methylene blue concentration is 10 mg / L, the degradation reaches the best efficiency within 120 minutes, which is a better choice. The dosage of 1# photocatalyst and the photocatalytic methylene blue degradation efficiency are summarized in Table 2.
[0091] Table 2
[0092] 1# Photocatalyst dosage (g / L) Degradation efficiency (%) 0.16 75.7 0.18 86.5 0.20 99.1 0.22 99.2 0.25 99.1 0.30 91.2
[0093] Using the above detection method, 100mL of methylene blue solution with concentration distribution of 10mg / L, 15mg / L, 20mg / L, 25mg / L and 27.5mg / L was poured into 5 beakers respectively, and then 20mg, 30mg, 40mg, 50mg and 55mg of 1# photocatalyst were added into 5 beakers respectively, and then the degradation rate of each methylene blue within 120 minutes was detected. The degradation rates were 99.1%, 98.8%, 99.2%, 98.5% and 88.7% respectively. It was found that within a certain range, when the concentration of methylene blue increased, Increasing the photocatalyst in the same proportion can achieve the highest degradation rate in the same time. However, when the methylene blue concentration reaches 27.5 mg / L, the degradation efficiency begins to decline, and the proportion of catalyst needs to be increased, which reduces the efficiency of the photocatalyst. In specific use, the methylene blue concentration needs to be controlled below 25 mg / L. While achieving the best degradation effect of methylene blue, the efficiency of the photocatalyst can also be guaranteed. However, when a higher degradation rate of methylene blue is not required, the concentration of methylene blue can be appropriately increased, and the amount of photocatalyst added can be adjusted as needed.
Claims
1. A method for producing a photocatalyst, characterized in that: The steps include: (1) grinding monazite tailings into monazite powder, then adding the monazite powder into nitric acid to completely dissolve the monazite powder, filtering to obtain a first filtrate and a first filter residue; adding oxalic acid solution to the first filtrate to produce oxalate precipitation, and when the precipitation is completed, filtering the solution to obtain a secondary filtrate and a secondary filter residue, and evaporating and drying the secondary filtrate to obtain a dopant; Calculated as oxides, the monazite tailings contain 20-32wt% ThO2, 2.2-3wt% CeO2, 1.5-2.2wt% TiO2, 1.6-2.3wt% P2O5, 0.6-0.9wt% La2O3, 0.4-0.6wt% PbO, and 0.2-0.3wt% ZrO2; (2) adding tetrabutyl titanate to anhydrous ethanol, then adding glacial acetic acid, and dripping hydrochloric acid to make the pH of the solution ≤ 3, and then mixing evenly to obtain solution A; adding a dopant to solution A, stirring evenly to obtain solution B; dropping an ethanol aqueous solution into solution B, and stirring continuously to obtain a sol; (3) The sol is aged at room temperature to obtain a gel, and then the gel is washed, dried, calcined and ground to obtain a photocatalyst.
2. The production method according to claim 1, characterized in that In step (1), the mass ratio of monazite powder to nitric acid is 1:(25-30), and the concentration of nitric acid is 60-68wt%; the mass ratio of monazite powder to oxalic acid is 1:(1.7-2.0), and the concentration of oxalic acid is 9-12wt%.
3. The production method according to claim 1, characterized in that In step (2), the mass ratio of tetrabutyl titanate, anhydrous ethanol and glacial acetic acid is 1:(3-5):(0.15-0.2).
4. The production method according to claim 1, characterized in that In step (2), the mass ratio of the dopant to tetrabutyl titanate is 1:(0.9-1.2) based on the monazite tailings.
5. The production method according to claim 1, characterized in that: In step (2), the ethanol aqueous solution is prepared from anhydrous ethanol and distilled water in a volume ratio of (3-5):1; the volume ratio of water to tetrabutyl titanate in the ethanol aqueous solution is (1-1.5):
1.
6. The production method according to claim 1, characterized in that: In step (3), the aging time of the gel is 20-30 hours, the drying temperature is 80-100° C., the drying time is 4-6 hours, the calcination temperature is 350-450° C., and the calcination time is 3-4 hours.
7. A photocatalyst prepared by the production method according to any one of claims 1 to 6.
8. Use of the photocatalyst according to claim 7 in wastewater treatment.
9. The use according to claim 8, characterized in that: The wastewater contains methylene blue, the concentration of methylene blue in the wastewater is 1-27.5 mg / L, and the concentration of the photocatalyst in the wastewater is 0.20-0.55 g / L.
Citation Information
Patent Citations
Method for preparing double rare-earth elements La and Y doped TiO2 photocatalyst
CN101721990A
Ce-Ag-TiO2 nano composite antibacterial material and preparation method thereof
CN111545200A